Does raised intraocular pressure begin in utero? - Foss, A; Rauf, A; Aihie Sayer, A; Evans, JR; Cooper, C; Wormald, R; Barker, D (1998)
AIM: To determine whether fetal and infant growth, as assessed by weight at birth and weight at 1 year, are related to intraocular pressure. METHODS: 717 men and women born in Hertfordshire between 1920 and 1930, for whom records of birth weight and weight at 1 year were available, were examined. Visual fields were assessed using the Takagi central 25 degrees 75 point static threshold screening program. Tonometry was performed using the Perkin's tonometer. The disc was assessed by direct ophthalmoscopy through dilated pupils. RESULTS: A significant inverse relation was found between systolic blood pressure and birth weight. However, no association was found between birth weight or weight at 1 year and intraocular pressure, cup/disc ratio, or visual field defects. CONCLUSIONS: There was no evidence to support fetal or infant growth as being important factors for the subsequent development of raised intraocular pressure.